SEYYED HOSSEIN NASSEYYED HOSSEIN NASR AND MODERN ISLAMIC THOUGHTR AND MODERN ISLAMIC THOUGHT - efendi, efendi; Gazali, Gazali (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This article aims to explore and analyze the dynamics of modern Islamic thought regarding the figure Seyyed Hossein Nasr. In the history of the development of modern Islamic thought, Seyyed Hossein Nasr is placed as one of the Islamic thinkers who was influential in the Islamic world. This figure is considered capable of bridging the differences in views between Sunnis and Shiites, so that the tension of thought between these two poles can be well reduced. Seyyed Hossein Nasr focuses on studying Islamic sciences in the context of societal change in the modern era. This article concludes that Seyyed Hossein Nasr's thinking is comprehensive and holistic. Nasr succeeded in seeing Islamic knowledge in one complete frame and interconnected and integrated with each other. This research is a type of qualitative research. The method used is descriptive analysis of Seyyed Hossein Nasr's thoughts taken from his primary works as well as from various secondary sources as support.